2020
DOI: 10.1111/nmo.13925
|View full text |Cite
|
Sign up to set email alerts
|

The effect of colonic tissue electrical stimulation and celiac branch of the abdominal vagus nerve neuromodulation on colonic motility in anesthetized pigs

Abstract: Background: Knowledge on optimal electrical stimulation (ES) modalities and regionspecific functional effects of colonic neuromodulation is lacking. We aimed to map the regional colonic motility in response to ES of (a) the colonic tissue and (b) celiac branch of the abdominal vagus nerve (CBVN) in an anesthetized porcine model. Methods: In male Yucatan pigs, direct ES (10 Hz, 2 ms, 15 mA) of proximal (pC), transverse (tC), or distal (dC) colon was done using planar flexible multi-electrode array panels and CB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 89 publications
5
17
0
Order By: Relevance
“…The copyright holder for this preprint this version posted February 25, 2022. ; https://doi.org/10.1101/2022.02.24.480770 doi: bioRxiv preprint implicated in the VNS-altered colonic physiological functions as we reported before 17 , suggesting that human colonic functions and neuromodulation could be modeled in the porcine.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…The copyright holder for this preprint this version posted February 25, 2022. ; https://doi.org/10.1101/2022.02.24.480770 doi: bioRxiv preprint implicated in the VNS-altered colonic physiological functions as we reported before 17 , suggesting that human colonic functions and neuromodulation could be modeled in the porcine.…”
Section: Discussionsupporting
confidence: 54%
“…The cross-comparison of the regional transcriptomic profiling between porcine and human indicates that the myenteric ganglia in proximal or distal colon express a conserved core gene program of orthologous genes from porcine to human with regional heterogeneity. Interestingly, VNS on the porcine modulates the conserved transcriptional program in the myenteric ganglia of proximal or distal colon, which may be implicated in the VNS-altered colonic physiological functions as we reported before 17 , suggesting that human colonic functions and neuromodulation could be modeled in the porcine.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Furthermore, the dominant frequencies (with most power/magnitude) of bio-impedance were identified and found to be shifted after the stimulation. The experimental results furthermore indicated the correlations between the proposed bio-impedance and the manometry approaches while dealing with the data reported in 23 , which demonstrates its potential application in colonic motility monitoring.…”
Section: Introductionmentioning
confidence: 56%
“…Electrical stimulation is a viable therapy for colonic motor disorders, particularly for patients who are refractory to traditional pharmaceutical treatments. As interest grows, a number of studies on colonic electrical stimulation have been conducted, which showed promising outcomes under different conditions 13 23 . In most of the current studies, the effectiveness of the technique was assessed mainly via colonic motility evaluation.…”
Section: Introductionmentioning
confidence: 99%